Pengaruh Konsumsi Makanan Mentah Khas Jepang Terhadap Kesehatan Mahasiswa SV IPB - Amri, Muhammad Yasir (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2024)
Raw foods are increasingly popular in today's society, especially among citizens who have a tendency to consume raw foods as part of a healthy lifestyle. However, there are concerns about the safety and health associated with the consumption of these raw foods. One of the countries that popularized raw food is Japan. Japan is a country that has its own characteristics especially in culture and society. The country makes several dishes such as sushi, sashimi and several other foods. Raw food has an attraction for domestic and foreign people who want to eat these dishes. Although some people are not compatible with this culture, there are also many people who really like dishes from this country. According to research, raw food or improperly cooked food is more at risk of bacteria and disease than cooked food. Sashimi, sushi or some other foods if processed in an unhygienic way and the wrong way of handling will cause some bacteria, especially salmonella bacteria. But on the other hand, raw food is one of the most popular foods in all ages and regions. So, it's good if you want to consume raw food, stick to the recommended portions.